Power in movement : social movements and contentious politics - Tarrow, Sidney G. (Cambridge studies in comparative politics., 2011)
"Social movements have an elusive power but one that is altogether real. From the French and American revolutions to the post-Soviet, ethnic, and terrorist movements of today, contentious politics exercises a fleeting but powerful influence on politics, society, and international relations. This study surveys the modern history of the modern social movements in the West and their diffusion to the global South through war, colonialism, and diffusion, and it puts forward a theory to explain its cyclical surges and declines. It offers an interpretation of the power of movements that emphasizes effects on the lives of militants, policy reforms, political institutions, and cultural change. The book focuses on the rise and fall of social movements as part of contentious politics in general and as the outcome of changes in political opportunities and constraints, state strategy, the new media of communication, and transnational diffusion"--